Modern information-communication technologies in education (MMIT Proceedings, 2025)
This article highlights the role of modern information and communication technologies (ICT) in the field of education, their significance and possibilities in improving the quality of education. Also analyzed are interactive educational tools, electronic textbooks, distance learning platforms, and technologies based on artificial intelligence. The article provides recommendations for the effective use of ICT in the educational process and examines the current state and future directions in the education system of Uzbekistan